If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 3(-5z + -3) = -5(5z + 6) + 3 Reorder the terms: 1 + 3(-3 + -5z) = -5(5z + 6) + 3 1 + (-3 * 3 + -5z * 3) = -5(5z + 6) + 3 1 + (-9 + -15z) = -5(5z + 6) + 3 Combine like terms: 1 + -9 = -8 -8 + -15z = -5(5z + 6) + 3 Reorder the terms: -8 + -15z = -5(6 + 5z) + 3 -8 + -15z = (6 * -5 + 5z * -5) + 3 -8 + -15z = (-30 + -25z) + 3 Reorder the terms: -8 + -15z = -30 + 3 + -25z Combine like terms: -30 + 3 = -27 -8 + -15z = -27 + -25z Solving -8 + -15z = -27 + -25z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '25z' to each side of the equation. -8 + -15z + 25z = -27 + -25z + 25z Combine like terms: -15z + 25z = 10z -8 + 10z = -27 + -25z + 25z Combine like terms: -25z + 25z = 0 -8 + 10z = -27 + 0 -8 + 10z = -27 Add '8' to each side of the equation. -8 + 8 + 10z = -27 + 8 Combine like terms: -8 + 8 = 0 0 + 10z = -27 + 8 10z = -27 + 8 Combine like terms: -27 + 8 = -19 10z = -19 Divide each side by '10'. z = -1.9 Simplifying z = -1.9
| w-3x-2y+2z=0 | | 4x15x1/2 | | 31y-(-1+10y)=-20 | | -6x=-3x-15 | | t=-16t^2+82t | | 9x-4=2t+3 | | 6y-23=14 | | -10(3-3x)+3(5x-4)=x | | 2X^2+4X+X=26 | | -2.2(y+14)=0.5(y+0.5) | | 208/6+8=x | | x+4-3=6(5) | | 5x^2+3x=6x^2+8 | | X+7-4=-2x+-5x+1 | | x-.12x=158400 | | -4v+20=-8v | | 2x+3y+2-y-5x-8= | | 4^2+8/2 | | 3(2x-5)=4(x-4)-6 | | 64a-21a= | | x=4x-4 | | 3(12-y)=8+3y | | -10z+9(4+3z)=x | | 61a-21a= | | 32=2+4+q | | 8+6+x=208 | | 4n-4=6n | | -4x-9=-87/7 | | 5(x+1)+2(2X^2+Y)-4(1-Y)+X^2= | | 8*6*w=208 | | b-8+4b=24 | | -9b-10=28 |